Investigation of genetic loci associated with parkinson's disease and the functional effect of LRRK2 mutations / Aroma Agape Gopalai - Aroma Agape, Gopalai (2016)
Parkinson’s disease (PD) is a progressive movement disorder which results in bradykinesia, rigidity, resting tremors and postural instability. The role of genetics in modulating the risk of developing PD has been highlighted through genome wide association studies (GWAS) and candidate gene screening. This thesis explores the extent to which variants identified through studies in Caucasian populations are also relevant to the Malaysian PD population. Fourteen variants spanning several different loci including the HLA-DRA, PARK16 and GAK/DGKQ loci and two genes, GRN as well as LRRK2 were screened. The HLA-DRA locus had a protective association with an odds ratio (OR) of 0.76 while the variants in PARK16 had OR values between 0.71 and 0.86. An association with GRN was not detectable in our Malaysian cohort but did show a significant risk association when a meta-analysis was performed with other ethnically matched PD cohorts. Five LRRK2 mutations (G2385R, R1628P, A419V, N551K and R1398H) were screened. The G2385R and R1628P mutations were found to be risk factors. We excluded A419V as a risk factor, and determined it as a rare variant in the Malaysian population. The N551K and R1398H mutations showed significant protective effects with OR values of 0.623 and 0.699 respectively. As the postulated protective role of N551K and R1398H has not been fully characterised functionally, we sought to further investigate this effect. Constructs of LRRK2 mutations (G2019S, N551K and R1398H) were transfected into human neuroblastoma (SH-SY5Y) cells. In cell viability assays, cells carrying the N551K and R1398H mutations were found to confer greater protection when exposed to cellular stress under hydrogen peroxide treatment compared to G2019S. As a kinase, LRRK2 is known to activate pathways that are triggered by cellular stress, initiating a cascade of cell death. In keeping with this, cells carrying the risk factor G2019S mutation showed higher kinase activity and lower cell viability, while the protective factor R1398H had the lowest kinase activity and iv higher cell viability. In addition, although R1398H is located on a domain that is responsible for GTPase activity, our data suggests that there is no significant effect on the GTP binding ability. Although cells expressing protective factor N551K showed high cell viability, the kinase and GTP binding activity was unaltered suggesting that it may use alternative pathway to confer protection. Collectively, this thesis represents the first investigation into genetic loci for PD in Malaysia and has revealed some insight into how selected variants within LRRK2 may influence protective mechanisms within neurons when exposed to cellular stress. Furthermore, while we are not yet at the stage of being able to provide diagnostic testing for late onset PD, the establishment of a Malaysian PD DNA bank achieved as part of this project will provide an invaluable resource for further genetic studies on the contribution of newly identified loci in our cohort.